Tinjauan Yuridis Terhadap Pelaku Peretasan Kartu Kredit (Carding) Menurut Undang-Undang Nomor 19 Tahun 2016 Tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik - Taroreh, Erwin; Libriany Tuasikal, Andhini Satya; Khairunissa Gobel, Ayu Suci; Salsabila, Khairunnisa; Umilasari, Dinda (Universitas Ekasakti, 2024)
Credit card hacking (carding) is a credit card fraud where the perpetrator knows someone's credit card number which is still valid for use, then the perpetrator can buy goods online where the bill can be addressed to the original owner of the credit card, while the perpetrator is called a carder.